2020
DOI: 10.3390/ph13050086
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked Fibroin Nanoparticles: Investigations on Biostability, Cytotoxicity, and Cellular Internalization

Abstract: Recently, crosslinked fibroin nanoparticles (FNP) using the crosslinker 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) or the polymer poly(ethylenimine) (PEI) have been developed and showed potentials as novel drug delivery systems. Thus, this study further investigated the biological properties of these crosslinked FNP by labeling them with fluorescein isothiocyanate (FITC) for in vitro studies. All formulations possessed a mean particle size of approximately 300 nm and a tunable zeta pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…Fibroin was extracted and purified from the raw Bombyx mori silkworm cocoons, following our previous studies (Pham et al., 2018 , 2019 , 2020 ). For this, the cocoons were degummed (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibroin was extracted and purified from the raw Bombyx mori silkworm cocoons, following our previous studies (Pham et al., 2018 , 2019 , 2020 ). For this, the cocoons were degummed (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The cell viability was determined using the MTS assay, with slight modification from a previous study (Pham et al. 2020 ). To this end, RAW 264.7 cells were seeded into a 96-well plate at a concentration of 5 × 10 3 cells/well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake studies were performed using A549 and RAW264.7 macrophage cell lines. 3,16 Briefly, 1 × 10 5 cells were seeded onto a sterile tissue culture-treated 48-well plate and cultured overnight to reach 80% confluency. Then, the cells were treated with 100 μg/mL of C6-SFN and incubated for 2 h at 37 °C and 5% CO 2 condition.…”
Section: Methodsmentioning
confidence: 99%
“…Fibroin is the main protein that exists in silk fibers. Due to its low immunogenicity, biodegradability, mechanical strength, significant productivity, and low cost, fibroin is an attractive material for nanoparticle generation [11,[56][57][58], especially for vehicles of sensitive biologicals such as insulin and growth factors. Kundu et al reported the fabrication of silk fibroin spherical nanoparticles as depots for VEGF [59].…”
Section: Silk Fibroinmentioning
confidence: 99%